Photochemistry and bio-evaluation of 1, 4- disubstituted tetrazolethiones and synthesis of 2-(2-(phenylimino) vinyl)benzonitrile - Chhabra, Radhika (Kansas State University, 2007)
Compounds containing the tetrazole scaffold have wide variety of applications in medicine, food industry, automobile industry, photography, agriculture. As a result, the structure and reactivity of these compounds have been studied. However, the related tetrazolethione scaffold has not been studied well. In our work presented in Chapter-1 (part-1), the synthesis, photochemical properties and reactivities of 1,4-disubstituted tetrazolethione analogs 20a-d are described. The solvent effects on the photochemistry of compounds are discussed and; the rates and quantum yields for the photodecomposition of compounds are documented. The photodecomposition products for the photolysis of 20a-d were analyzed by LCMS, GCMS and NMR spectroscopy; the results pertaining to their identification are also reported. Further, the multiphoton excitation of THF solution of 1-methyl-4-(4-nitrophenyl)-1H-tetrazol-5(4H)-thione 20d with Ti: Sapphire laser was also performed; however, the experiment was not successful. In Chapter-2 (part-1), the cytoxicity of the 1-methyl-4-(4-chlorophenyl)-1H-tetrazol-5(4H)-thione 20c against human breast cancer cell is documented. MTT assays were performed for a time dependent study of the cytoxicity. In part-2 which consists of Chapter-3, the synthesis of 2-(2-phenylimino)vinyl)benzonitirle is described. This was as a step towards our laboratory's goal of synthesizing a series of mono-, di- and tri- azaenyne-allenes and studying their Myers-Saito and Schmittel cyclizations. In future, if our cyclization studies are successful, these cyclizations could be employed for synthesis of heteroaromatic rings found in many compounds of biological importance.
Keywords: tetrazolethione; Chemistry, Organic (0490)